Incidence of biliary complications in living donor liver transplantation - Varghese, Joseph (International Journal of Research in Medical Sciences, 2018)
Background: Liver transplantation is a widely accepted treatment for end stage liver diseases and selected cases of hepatocellular carcinoma, if it is limited to the liver. Biliary complications such as biliary strictures and bile leaks after the liver transplantation remain the major cause for morbidity and mortality. This study was aimed to estimate the incidence of biliary complications in live donor liver transplantation (LDLT) patients and the rate of radiological intervention in its management. Methods: Case records of LDLT patients during the past two years were retrospectively studied to estimate the incidence of biliary complications. Biliary complications were diagnosed based on clinical features like pain, fever, jaundice or increased bile from biliary drains. The patients were imaged using ultrasonogram, computed tomogram, magnetic resonance imaging or Endoscopic retrograde cholangiopancreatography (ERCP) for any biliary strictures and leaks, choledocholithiasis or sphincter of oddi dysfunction. The rate of ERCP and Percutaneous Trans Biliary Drainage (PTBD) interventions in these patients was recorded. Results: Fifty cases of post LDLT patients (both prospective and retrospective) were analysed in the study. The incidence of biliary stricture was 12% (6/50) and among the 6 patients with biliary stricture, 4 had bile leak. Among the total cases, the incidence of biliary leak was 8%. Eighty three percent of the biliary complications were managed by ERCP, whilst 17% by PTBD. Conclusions: The incidence of biliary stricture was 12% and biliary leak was 8%. The biliary complications were managed by ERCP in 83% and percutaneous approach in 17% of cases.